2018
DOI: 10.1007/s10620-018-4947-1
|View full text |Cite
|
Sign up to set email alerts
|

Adenoma Detection Rate Falls at the End of the Day in a Large Multi-site Sample

Abstract: In our study population, ADR and withdrawal time decrease by roughly 7 and 20%, respectively, by the end of the day. Our results imply that rather than mental or physical fatigue, lower ADR at the end of the day might be driven by endoscopists rushing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Our known data analysis found a significant association between the time of day that a colonoscopy is performed and mean WT, with lower times later in the day, culminating in an increased proportion with a WT less than 6 min. This finding is in agreement with Marcondes et al, who found a roughly 20% reduction in WT from the first to last colonoscopy of the day [ 8 ]. A decline in ADR and PDR was also apparent in colonoscopies performed later in the clinic schedule.…”
Section: Discussionsupporting
confidence: 93%
“…Our known data analysis found a significant association between the time of day that a colonoscopy is performed and mean WT, with lower times later in the day, culminating in an increased proportion with a WT less than 6 min. This finding is in agreement with Marcondes et al, who found a roughly 20% reduction in WT from the first to last colonoscopy of the day [ 8 ]. A decline in ADR and PDR was also apparent in colonoscopies performed later in the clinic schedule.…”
Section: Discussionsupporting
confidence: 93%
“…5,6 ADR varies dramatically among different endoscopists (7%-53%) 7 and also for each operator during the course of the day (approximately 7%), probably due to the intrinsic imprecision of the human eye brought about by fatigue and rush activities. 8 New technologies have been reported in the literature to improve ADR, including enhanced optics, distal attachments, cap-assisted techniques, and balloon-assisted devices, with the goal of improving mucosa visualization and eventually diagnosing hardly detectable polyps. 9 By aiding polyp detection on colonoscopy images (Figs.…”
Section: Introductionmentioning
confidence: 99%
“…Higher ADR is associated with lower interval CRCs and lower CRC mortality [ 5 , 6 ]. ADR varies dramatically among different endoscopists (7%–53%) [ 7 ] and also for each operator during the course of the day (approximately 7%), probably due to the intrinsic imprecision of the human eye brought about by fatigue and rush activities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…), light reflection of normal mucosa and feces. One study reported that a colonoscopist achieves a polyp detection rate ranging from 7% to 20% in a day 21 . Previous studies have suggested that additional observers are helpful in reducing the misdetection of visible polyps 22–24 .…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that a colonoscopist achieves a polyp detection rate ranging from 7% to 20% in a day. 21 Previous studies have suggested that additional observers are helpful in reducing the misdetection of visible polyps. [22][23][24] Given the low falsepositive rate and high sensitivity, the CADe algorithm may assist colonoscopists to improve their performance and ultimately benefit patients.…”
Section: Discussionmentioning
confidence: 99%